Dual Genetic Encoding of Acetyl‐lysine and Non‐deacetylatable Thioacetyl‐lysine Mediated by Flexizyme. Issue 12 (23rd February 2016) - Xiong, Hai; Reynolds, Noah M.; Fan, Chenguang; Englert, Markus; Hoyer, Denton; Miller, Scott J.; Söll, Dieter
Abstract: Acetylation of lysine residues is an important post‐translational protein modification. Lysine acetylation in histones and its crosstalk with other post‐translational modifications in histone and non‐histone proteins are crucial to DNA replication, DNA repair, and transcriptional regulation. We incorporated acetyl‐lysine (AcK) and the non‐hydrolyzable thioacetyl‐lysine (ThioAcK) into full‐length proteins in vitro, mediated by flexizyme. ThioAcK and AcK were site‐specifically incorporated at different lysine positions into human histone H3, either individually or in pairs. We demonstrate that the thioacetyl group in histone H3 could not be removed by the histone deacetylase sirtuin type 1. This method provides a powerful tool to study protein acetylation and its role in crosstalk between post‐translational modifications. Abstract : Director's cut : The Flexizyme technique is used to incorporate acetyl‐lysine and the non‐hydrolyzable thioacetyl‐lysine into full‐length proteins in vitro and site‐specifically into human histone H3, either individually or in pairs. The thioacetyl group of the modified histone H3 could not be removed by the histone deacetylase sirtuin.